2018
DOI: 10.1002/jwmg.21558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of distribution, behavior, and climate on mule deer survival

Abstract: Mule deer (Odocoileus hemionus hemionus) populations in North America are a valuable economic wildlife resource, with the managed harvest of this species reflecting societal values and recreational opportunities in many parts of the western United States. Managing mule deer populations while allowing for harvest requires an understanding of the species’ population dynamics, including the specific factors associated with population change. We conducted a 7‐year (2005–2012) study designed to investigate habitat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
0
15
1
Order By: Relevance
“…(Sawyer et al, 2016) + (Nicholson et al, 1997) ? (Sawyer et al, 2016;Schuyler et al, 2019) + (Nicholson et al, 1997)…”
Section: Odocoileus Hemionusmentioning
confidence: 99%
See 1 more Smart Citation
“…(Sawyer et al, 2016) + (Nicholson et al, 1997) ? (Sawyer et al, 2016;Schuyler et al, 2019) + (Nicholson et al, 1997)…”
Section: Odocoileus Hemionusmentioning
confidence: 99%
“…The Terminal Investment Hypothesis states that older (past their prime) individuals are more likely to devote more resources toward ensuring successful reproduction than younger (yearling or prime-aged) individuals because they anticipate fewer future reproductive events (Clutton-Brock et al, 1982;Clutton-Brock, 1984;Bercovitch et al, 2009). When applied to migration, this hypothesis predicts that ungulates might have a propensity to remain resident while young so as to prioritize their own survival by avoiding risks that can occur during migration (e.g., from predation or anthropogenic factors; Nicholson et al, 1997;Hebblewhite and Merrill, 2011;Schuyler et al, 2019); as they age, they might accept greater risks to migrate to increase access to resources for investment in their terminal offspring (Fryxell and Sinclair, 1988a;Albon and Langvatn, 1992). The age at which this hypothesis might occur in ungulates could be quite old; indeed, Eggeman et al (2016) showed potential evidence that elk became more likely to migrate with age in Alberta, Canada, but migrants rarely switched to a resident tactic after aging (>15 years old).…”
Section: State and Physiological Conditionmentioning
confidence: 99%
“…In New Mexico, USA, nutritional limitations and drought on summer and early autumn range caused female mule deer to enter winter with low body fat and was the best predictor of survival (Bender et al 2007). In south-central Oregon, mule deer that migrated to higher elevation summer range (i.e., forested communities) had higher survival rates than those mule deer that were resident on winter range (i.e., juniper woodlands and sagebrush cover types) yearround (Schuyler et al 2019). Mule deer typically migrate from low elevation winter ranges to higher elevation summer ranges for increased foraging opportunity (D'Eon and Serrouya 2005, Monteith et al 2011).…”
mentioning
confidence: 99%
“…Past studies have linked the survival of large herbivores to weather patterns, vegetation, predation risk (Bender, Lomas, & Browning, ; DeCesare et al, ) and other factors known to directly affect or index nutritional condition (Bishop, White, Freddy, Watkins, & Stephenson, ; Monteith et al, , ). Furthermore, some studies have suggested migratory ungulates have lower rates of survival than their resident counterparts (Nicholson, Bowyer, & Kie, ; Schuyler, Dugger, & Jackson, ), and within the migratory segment, those that migrate further may encounter more anthropogenic risks (Sawyer, Middleton, Hayes, Kauffman, & Monteith, ). Expanding this growing body of work to understand how mortality risk might be influenced by various migratory parameters could further solidify the connection between migration and demography, and importantly, refine our ability to detect, and potentially mitigate, previously unknown risk factors that regulate large herbivores populations.…”
Section: Introductionmentioning
confidence: 99%